Slope Gradient Controls Soil Thickness and Chemical Weathering in Subtropical Brazil: Understanding Rates and Timescales of Regional Soilscape Evolution Through a Combination of Field Data and Modeling. Issue 6 (1st June 2020) - Brosens, Liesa; Campforts, Benjamin; Robinet, Jérémy; Vanacker, Veerle; Opfergelt, Sophie; Ameijeiras‐Mariño, Yolanda; Minella, Jean P. G.; Govers, Gerard
Abstract: Soil thickness and residence time are regulated by a dynamic interplay between soil formation and lateral transport of soil particles and solutes. To unravel this interplay and infer patterns and rates of chemical weathering, soil physical and chemical properties can be used. Here, we present an integrated approach combining numerical modeling with field measurements to assess the impact of slope gradient on soil thickness and chemical weathering at a regional scale. We first perform a number of synthetic model runs simulating soil formation, weathering, erosion, and deposition, which show that soil thickness and weathering degree decline with increasing slope gradient. We then evaluate how those functional relationships compare to soil‐landscape data observed in the field. Soils are sampled at 100 midslope positions under varying slope gradient. The weathering degree is determined using three chemical weathering indices: ratio of iron oxides to total iron ( Fe d /Fe t ), chemical index of alteration ( CIA ), and total reserve in bases ( TRB ). Finally, we calibrate the Be2D model to our field data to constrain soil residence times and chemical weathering rates. The modeled weathering rates decrease with increasing soil residence time and decreasing slope gradient. The application of the soil‐landscape evolution model in Southern Brazil shows that weathering rates can vary up to 2 orders of magnitude and depend on hillslope gradient. Notwithstanding model limitations and data uncertainties, we demonstrate the potential of an integrated approach, where field data and numerical modeling are integrated to unravel the timescale of soil weathering along transport over hillslopes. Plain Language Summary: By combining a numerical soil‐landscape evolution model with field data we assess the impact of topography on soil thickness and chemical weathering degrees and rates. Chemical weathering degrees are indicative of the extent of chemical weathering of the soil mantle, whereas weathering rates indicate how fast the chemical composition is changing over time. We show that on steep slopes soils are thinner and have a lower weathering degree compared to gentle slopes. The observed difference in soil weathering is related to the soil residence time, which is constrained by combining field measurements with a numerical model. Soils developed on basalt and dacite‐rhyolite rocks in a subtropical climate regime have soil residence times ranging between 20 and 1700 kyr. Soils on steep slopes are younger and characterized by weathering rates that can be twice as high as for older soils on gentle slopes. Integrating field data in soil‐landscape evolution models can help to unravel the interplay between topography, soil erosion, and weathering in soil‐mantled landscapes. Key Points: Soil thickness and weathering degree decrease with increasing slope gradient Combining a numerical model with field data enabled us to constrain soil residence times between 20 and 1700 kyr, which strongly decrease with increasing slope gradient Simulated weathering rates might vary by 2 orders of magnitudes and increase with increasing slope gradient and erosion rate